Implementation of learning strategies for students in large classes. - Salazar Pilco, Carla Michelle (2023)
The analysis of this case study that was carried out at the Unidad Educativa Americano highlighted important points that achieved the completion of the same, with the help of the tutor teacher of the English area of the 8 "c", it was possible to capture the advantages and disadvantages that students have when acquiring a new language such as English, also the methodologies that work best for a large group of students were analyzed. The objective of this case study is to try to understand and give solutions to the needs of the students through a teaching method more enjoyable to them and not the traditional method, taking into account that some students require different learning strategies, also encouraging them that learning English can also be fun, facilitating learning in a dynamic way and capturing their attention.